PRESTASI BELAJAR MAHASISWA PROGRAM STUDI PAI FITK UIN RADEN FATAH PALEMBANG ANGKATAN 2014 DALAM MATA KULIAH BAHASA ARAB - Abdurrahmansyah Abdurrahmansyah; Ismail Sukardi; Nyayu Soraya (Tadrib: Jurnal Pendidikan Agama Islam, 2017)
The curriculum is based on the State Islamic University Raden Fatah Palembang, Arabic courses included in Component (MKU) to be followed by all students of various faculties and pogram Studies. While Raden Fatah Palembang UIN Students come from a variety of different educational backgrounds some of which comes from MAN and SMU. Among them there are already studying Arabic and some have not even never at all to learn Arabic because their school curriculum tailored to each. Therefore whether their learning achievement in the subject of Arabic was also no difference, then there should be research to prove it.The purpose of this study was to determine differences in the achievement of students whose educational background Madrasah Aliyah (MAN) and student backgrounds of State High School (SMU) in the subject of Arabic.Starting from the idea of achievement (output) students in learning that can be influenced by various components one of which is the input that students with a variety of factors that influence both internally and externally. The hypothesis proposed in this study was the difference in the achievement of students who come from MAN and students from SMU in the course Arabic.The method used in this research is descriptive analysis method to study the documentation. The analysis of the data using a statistical approach to the bivariate komparasional techniques. Once the data is analyzed, the results showed that the two variables are students who come from MAN and students from SMU, equally distributed normally, as well as two variations equally homogenous and then later on the results of hypothesis testing using the formula t and results hypothesis testing indicate that Ho is accepted and Ha rejected.Thus we can conclude that the achievement of students whose educational background Madrasah Aliyah (MAN) and student educational background School of Public Affairs (SMU) in the subject of Arabic turns out the difference is not significant. It means that there is a difference between the two although the difference was very little. So it means that students from SMU can follow courses in Arabic.